Tailoring the Performances of Lead Halide Perovskite Devices with Electron‐Beam Irradiation. Issue 34 (6th July 2017) - Yi, Ningbo; Wang, Shuai; Duan, Zonghui; Wang, Kaiyang; Song, Qinghai; Xiao, Shumin
Abstract : Lead halide perovskites are intensively studied in past few years due to their potential applications in optoelectronic devices such as solar cells, photodetectors, light‐emitting diodes (LED), and lasers. In addition to the rapid developments in material synthesis and device fabrication, it is also very interesting to postsynthetically control the optical properties with external irradiations. Here, the influences of very low energy (10–20 keV) electron beam of standard electron beam lithography are experimentally explored on the properties of lead halide perovskites. It is confirmed that the radiolysis process also happens and it can selectively change the photoluminescence, enabling the direct formation of nanolaser array, microsized light emitter array, and micropictures with an electron beam writer. Interestingly, it is found that discontinuous metallic lead layers are formed on the top and bottom surfaces of perovskite microplate during the radiolysis process, which can act as carrier conducting layers and significantly increase the photocurrent of perovskite photodetector by a factor of 217%. By using the electron beam with low energy to modify the perovskite, this method promises to shape the emission patterns for micro‐LED with well‐preserved optical properties and improves the photocurrent of photodetector. Abstract : A simple approach to tailor the optical properties of lead halide perovskite devices is presented. In contrast to conventional studies within transmission electron microscopy, it is shown for the first time that the MAPbBr3 perovskites and their devices can be simply patterned and improved via electron‐beam irradiation in an electron‐beam writer or a scanning electron microscope with relatively low accelerating voltage.